The Selection of High-Skilled Migrants - Jens Ruhose; Matthias Parey; Fabian Waldinger; Nicolai Netz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We investigate international migration choices of high-skilled individuals and measure migrant selection using predicted earnings. High-skilled migrants select to destinations as predicted by Borjas' (1987) model of migration choices. Migrants to less equal countries are positively selected, while migrants to more equal countries are negatively selected, relative to non-migrants. For our analysis, we use a survey of university graduates, including detailed information on background characteristics, university studies, and labor market choices, combined with measures of earnings inequality for high-skilled individuals in destination countries. Our rich data allow us to decompose the observed selection patterns. Positive selection to less equal countries is driven by university quality and grades. Negative selection to more equal countries is driven by university subject and gender. Our results highlight the relevance of the Roy/Borjas model for high-skilled individuals in a setting where credit constraints and other barriers to migration are unlikely to be binding.
Keywords: F22; J24; J61; 330